Quality of life of individuals receiving kidney transplantation in Amazonas State - Eliza Dayanne de Oliveira Cordeiro; Tatiana Castro da Costa; Monique Figueiredo Teixeira; Noeli das Neves Toledo; Gilsirene Scantelbury de Almeida
Abstarct Objective: to analyze the quality of life of kidney transplant receivers in the State of Amazonas. Method: a cross-sectional, descriptive study, performed with 222 individuals after renal transplantation registered in a private clinic and in a health public ambulatory. Data collection took place through structured interviews where the quality of life was measured by the Kidney Disease Quality of Life - Short Form. Descriptive statistics were used for data analysis. Results: the quality of life scores found ranged from 36.5 to 83.1. The quality of life domains, specifics of renal disease, have proved to be superior to generic ones. The most compromised were work situation; sleep; physical function and emotional function, with scores of 36.5; 53.7; 52.4; 55.1, respectively, and correlated moderately and significantly with each other. Conclusion: the majority (63.2%) of the quality of life domains obtained high scores and the specific component of renal disease had higher scores than the generic component.